Therapeutic Approaches to Gastric Hepatoid Adenocarcinoma: Current Perspectives - Søreide JA (Dove Medical Press, 2019)
Jon Arne Søreide1,2 1Department of Gastrointestinal Surgery, Stavanger University Hospital, Stavanger, Norway; 2Department of Clinical Medicine, University of Bergen, Bergen, NorwayCorrespondence: Jon Arne SøreideDepartment of Gastrointestinal Surgery, Stavanger University Hospital, POB 8100, Stavanger N-4022, NorwayTel +47 905 31770Fax +47 51519919Email jonarne.soreide@uib.noAbstract: Hepatoid adenocarcinoma of the stomach (HAS) is a rare subgroup of gastric cancer (GC). Morphologically, this tumor exhibits both adenocarcinomatous and hepatocellular differentiation, and most tumors show immunohistochemical staining for alpha-fetoprotein (AFP) or elevated AFP serum levels. The diagnosis of HAS is frequently delayed, and at least half of patients have advanced disease at the time of diagnosis. Despite a lack of evidence, treatment approaches have mostly followed principles for the treatment of common gastric cancer (CGC), including radical surgery in eligible patients with curative intent. The indications for and the type of adjuvant systemic treatments remain unclear. Additionally, there is a lack of evidence allowing any firm conclusions to be drawn regarding the best treatment for patients with metastatic HAS (mHAS). Chemotherapy regimens, including cisplatin-based chemotherapy, are considered the most efficient first-line systemic treatment in advanced situations. Their combination with targeted therapy (i.e., trastuzumab) in HER2-positive tumors seems promising. The rarity of these patients and the scarce and heterogeneous literature on this particular subgroup of GC make it difficult to provide any robust evidence for the clinical management of patients with HAS.Keywords: hepatoid adenocarcinoma, stomach, gastric, alpha-fetoprotein, therapy, prognosis